PENGARUH LINGKUNGAN FISIK TERHADAP TINGKAT KUNJUNGAN WISATAWAN DI MUSEUM DAERAH SANG NILA UTAMA KOTA PEKANBARU - Tharra Amalia; Hendro Ekwarso; Taryono ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
The purpose of this study was to determine the influence of the physical environment of the level visit of tourist at Museum Daerah Sang Nila Utama Pekanbaru City. Museum Daerah Sang Nila Utama is one of the cultural attractions in Pekanbaru city. The sampling technique used was accidental sampling with a sample of 100 people. This study analysis by used descriptive quantitative through the stages of scoring using a Likert scale and simple linear regression. In this study, the independent variable is the physical environment and the dependent variable is the level visit. The results showed gains the highest score on the physical environment variables exterior facility located on the indicator landscape amounted to 79.8%, the lowest score on this indicator exterior design amounted to 64.5%. While the interior facility, the highest score is the indicator of the layout amounted to 78.5% and the lowest scores on the temperature indicator air quality at 53.8%. While at variable level visit, the highest score is the indicator of choice museum’s name 75.2%, and the lowest score on indikator amount of visits by 54.0%. The test results using simple linear regression showed that the physical environment significantly influence to the level visit of tourist at the Museum Daerah Sang Nila Utama Pekanbaru City, R square value of 0.659 and a correlation coefficient of 0.812, which means that both variables have a very strong correlation.Keywords : Physical Environment, Level Visit, Exterior Facility, Interior Facility.